Analysis of Slope Stability with Wire Mesh and Nailing as Slope Protection System Using Finite Element Method (PLAXIS) - Ayob, Mohamad; Shafee, Nurliyana; Salleh, Khairul; to Amiri, Shin; Kasa, Anuar (International Journal of Engineering and Technology, 2019)
This study is based on the slopes at Ulu Jelai Ringlet, Pahang. The slope stability assessment is carried out by using finite element modeling with the approach of PLAXIS software with activation of slope protection system application to a cut slope. From the analysis, it is found that the factor safety of the slope is 1.395, less stable and lower than the allowable FOS which is 1.50. Stabilization methods, wire mesh nailed to slope are proposed to improve the slope stability. The assessment results by the software with the application of stabilization methods proposed showed an increase in the value of factor of safety and decrease in soil displacement. The slope with 60Ëš inclination of cut slope with activation of wire mesh and soil nail obtained an overall factor of safety 2.831 satisfied the highest minimum requirement for both risk of life and economic risk. The reinforcement reduced displacements of the soil surface, increased the slope stability. The tension in the mesh is concentrated in the point where the mesh is nailed to the slope. The axial force is higher in the nailed points situated in the lower point of the slope. Total displacement occur more in soil 1 (soft clay) due to the stiffness of soil. The effect of the nailed mesh makes it possible to reach higher slope height without failure, than if the construction is done without reinforcement. This proved that the proposed stabilization methods can be implemented to improve the slope stability. Some remedial and maintenance works were recommended to improve the slope stability.